Osteometric sex estimation from the os coxa in a Thai population - Mahakkanukrauh P. (2017)
© 2016 Elsevier Ireland Ltd The coxal bone shows a very high degree of sexual dimorphism both morphologically and metrically. However, despite a number of recent studies on sex estimation from the skeleton in Thailand, no osteometric methods o f sexing the Thai os coxa have been proposed. Therefore, the aim of this study was to develop a standard sex estimation method for a Thai population by examining the efficacy of six coxal bone measurements and eight indices obtained from 200 Thai skeletons. Independent samples t-tests revealed statistically significant differences between males and females for all but one of the measurements. The equation with the highest correct allocation accuracy was based on four measurements (pubis length, ischium length, total height and acetabulum diameter) and had a predicted and cross-validated accuracy of 96.9% and a tested accuracy of 97.5% on a holdout sample of 40 individuals. The single variable equation with the highest correct allocation accuracy of 94.4% and a tested accuracy of 97.5% was for the ischiopubic index, which is calculated from ischium length and pubis length. Percentage accuracies in predicting sex from these equations were higher than many previous studies, suggesting high levels of sexual dimorphism in the Thai os coxa.